On the Three-Dimensional Contact Problem of a Rigid Inclusion Pressed Between Two Elastic Half-Spaces - G.M.J. Damen (Engineering Transactions, 1977)
An approximation solution is found for the three-dimensional contact problem of two elastic half-spaces pressed against each other with a rigid inclusion between them. We confine ourselves to identical spaces nad will examine an inclusion of a such a nature that rotational symmetry is achieved.